2004
DOI: 10.4049/jimmunol.173.2.1292
|View full text |Cite
|
Sign up to set email alerts
|

Differential Induction of IL-1β and TNF by CD40 Ligand or Cellular Contact with Stimulated T Cells Depends on the Maturation Stage of Human Monocytes

Abstract: Cellular contact with stimulated T cells potently induces cytokine production in monocytes, a mechanism that is likely to be relevant to chronic inflammation. Although the identity of surface molecules involved in this process remains elusive, CD40 and its ligand, CD40L, are thought to be implicated, considering that they are expressed at the inflammatory site. To ascertain the involvement of CD40L, we compared the activation of three different types of human monocytic cells, i.e., freshly isolated monocytes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 38 publications
2
27
1
1
Order By: Relevance
“…Previous studies demonstrated that fixed, stimulated HUT-78 cells, plasma membranes of the latter cells, and CEsHUT display similar ability to induce cytokine production in human monocytes (15). To activate monocytes, CE sHUT was used at either 1 g/mL or 6 g/mL proteins as previously determined (38,44).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that fixed, stimulated HUT-78 cells, plasma membranes of the latter cells, and CEsHUT display similar ability to induce cytokine production in human monocytes (15). To activate monocytes, CE sHUT was used at either 1 g/mL or 6 g/mL proteins as previously determined (38,44).…”
Section: Methodsmentioning
confidence: 99%
“…HUT-78 cells (2 ϫ 10 6 cells/mL) were stimulated for 6 h by phytohemagglutinin (1 g/mL) and PMA (5 ng/mL). Plasma membranes of stimulated HUT-78 cells were prepared as previously described and solubilized in 8 mM CHAPS (23,44). CHAPS extract of membranes of stimulated HUT-78 cells was referred as to CE sHUT.…”
Section: Methodsmentioning
confidence: 99%
“…17 Increased surface expression of the CD40 receptor on MDS monocytes could account for this different behavior, but also activation of different downstream pathways might be responsible. 30 This remains to be explored. In addition, we analyzed the effects of inhibiting this pathway in colony formation assays, using the monoclonal antibody ch5D12, which is an antagonist chimeric anti-human CD40 antibody that has been shown to be effective in the therapy of inflammatory bowel disease 22 and non-human primate models of autoimmune encephalomyelitis.…”
Section: Discussionmentioning
confidence: 99%
“…The CD40 receptor is a 45-50 kDa type I phosphoprotein that is a member of the TNF receptor superfamily. It has been demonstrated that monocytes express low levels of CD40, 30 but expression of the CD40 gene is induced upon activation, which is most pronounced by stimulation with IFN-g. 27 Besides production of TNF-a, CD40 ligation also results in the secretion of other pro-inflammatory cytokines and chemokines such as IL-1, IL-6, IL-8, IL-10, IL-12 and macrophage-inflammatory protein-1a. 18,19 In addition, ligation of CD40 by CD40L, present on T helper cells, promotes upregulation of co-stimulatory molecules (CD40, CD80, CD86, MHC class II molecules) and FasL.…”
Section: Discussionmentioning
confidence: 99%
“…HUT-78 cells were cultured and activated by PHA (1 µg/ml) and PMA (5 ng/ml) in RPMI 1640 medium supplemented with 10% heat activated FCS, 50 µg/ml streptomycin, 50 U/ml penicillin, 2 mM glutamine (complete RPMI medium) in a 5% CO 2 -air humidified atmosphere at 37°C as described elsewhere [34]. Plasma membranes of stimulated HUT-78 cells were isolated and solubilized with CHAPS to obtain membrane CHAPS extract (CE sHUT ) as previously described [35].…”
Section: T Cells and Preparation Of T Cell Plasma Membranesmentioning
confidence: 99%